The Prevalence and Associated Factors of Depressive Symptoms Among Medical Students in Bangladesh During the COVID-19 Pandemic: A Cross-Sectional Pilot Study - Biswas, Md. Abdullah Al Jubayer; Hasan, M. Tasdik; Samir, Nora; Alin, Sayma Islam; Homaira, Nusrat; Hassan, Md. Zakiul; Khatun, Mst Rabeya; Anjum, Afifa; Hossain, Sahadat; Koly, Kamrun Nahar; Safa, Farhana; Alam, Syeda Fatema; et al. (Frontiers in Public Health, 2022)
Background: Whilst very limited studies have demonstrated a correlation between the COVID-19 pandemic and depressive symptoms amongst Bangladeshi medical students, the prevalence and associated factors of depressive symptoms as measured by the Patient Health Questionnaire (PHQ-9) remains widely unknown. Objective: The study aimed to investigate the prevalence and factors associated with depression symptoms among Bangladeshi medical students during the COVID-19 pandemic lockdown period. Method: In this web-based cross-sectional pilot study, medical students' data was collected using the Google Forms web survey platform after obtaining informed consent. A total of 425 medical students were selected using a systematic sampling technique to accumulate depression symptoms and demographic and pandemic-related information. Depression was measured by a self-administered, validated English version of the Patient Health Questionnaire (PHQ-9) tool. The descriptive analysis utilised frequency and percentages, while the stepwise binary logistic regression analysis was performed to investigate the factors associated with depressive symptoms. Result: Among 425 medical students, 62.3% were female, 97.4% unmarried. Almost 80.2% of medical students had mild to severe levels of depressive symptoms as characterised by PHQ-9. A significantly higher probability of depression was found amongst female students (adjusted OR =1.8), those who struggled to stay away from social media (adjusted OR=1.8), those who tried to be optimistic for maintaining better psychology (adjusted OR=11.1), and those who always had a sleeping difficulty in the last four weeks (adjusted OR=8.9). Conclusion: A very high prevalence of depression symptoms among Bangladeshi medical students was found across the majority of socio-demographic variables. The alarming prevalence and associated factors of depression suggests the need for follow-intensity psychosocial interventions designed for medical students during the COVID-19 pandemic